2010
DOI: 10.1073/pnas.1003052107
|View full text |Cite
|
Sign up to set email alerts
|

Quantum computing with defects

Abstract: Identifying and designing physical systems for use as qubits, the basic units of quantum information, are critical steps in the development of a quantum computer. Among the possibilities in the solid state, a defect in diamond known as the nitrogen-vacancy (NV −1 ) center stands out for its robustness-its quantum state can be initialized, manipulated, and measured with high fidelity at room temperature. Here we describe how to systematically identify other deep center defects with similar quantum-mechanical pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
606
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 703 publications
(627 citation statements)
references
References 43 publications
16
606
1
4
Order By: Relevance
“…3 These favorable properties have stimulated a search for analogous defects in materials other than diamond. 4 One obvious candidate material is silicon carbide, a compound that is closely related to diamond in structure and bonding.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 These favorable properties have stimulated a search for analogous defects in materials other than diamond. 4 One obvious candidate material is silicon carbide, a compound that is closely related to diamond in structure and bonding.…”
mentioning
confidence: 99%
“…7 Recent theoretical work has identified the N C -V Si center in 4H-SiC as a promising candidate for qubit applications. 4,5 First-principles calculations and experimental measurements have also indicated that the neutral divacancy in 4H-SiC has desirable properties 8-10 (see Fig. 1): photoluminescence, angleresolved magneto-luminescence, and continuous-wave optically-detected magnetic resonance (ODMR) measurements have demonstrated room-temperature spin control, with spin-coherence properties comparable to those of the NV center in diamond.…”
mentioning
confidence: 99%
“…Finally NV centres, even if not discussed here, occupies a special place as possible fl ying qubit for remote entangling of spin qubits in solid state, due to its optical-spin polarization properties and its possible integration in quantumhybrid-spin systems (e.g., NV and magnetic single molecules). Other deep centres as NV centre in diamond and in similar wide-bandgap semiconductors, such as SiC are under investigation [18,66] ; we are witnessing either a new era of research of another NV-like centre in solid state or the establishing of novel advanced technologies in the above-mentioned fi elds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed this issue both experimentally [14,15] and theoretically [16] . Furthermore, other atom-like defects can potentially be engineered in diamond [17] and other materials [18] with similar or perhaps better properties suitable for the desired applications.…”
Section: Introductionmentioning
confidence: 99%
“…1 Examples of nuclear-electron spin complexes include those formed within self-assembled semiconductor quantum dots, 2 in the vicinity of crystal defects such as the nitrogen-vacancy center in diamond, 3 the divacancy and silicon-vacancy centers in SiC, 4,5 substitutional phosphorous 6 and bismuth 7 in silicon, rare-earth ions, 8 and others. 9 Systems formed by trapped photoexcited electrons and neighboring nuclear spins in semiconductors form a subclass of spin complexes with interesting properties. For example, because these defects often change from paramagnetic to magnetically inactive once the trapped photoelectron recombines, nuclear spins in the vicinity are inherently protected against electron-spin-induced decoherence.…”
Section: Introductionmentioning
confidence: 99%